PENGGUNAAN MINYAK SAWIT MERAH DAN JENIS BAHAN PENSTABIL TERHADAP KARAKTERISTIK DAN KANDUNGAN KAROTENOID ES KRIM - Tunggal Putri, Velly Yanti; Hidayati, Sri (Kementerian Perindustrian, 2016)
Abstrack : Ice cream is a kind of semi-solid food made from a mixture of milk , animal and vegetable fat , sugar, with or without other food additives . Milk fat make ice cream has a soft texture. Milk fat can be replaced with vegetable fat/ vegetable oil such as Red Palm Oil (RPO). The purposes of this research are to determine the effect of RPO and milk formulation as well as the type of stabilizer on the ice creamÂ characteristics and carotenoid total and find out the interaction between them . The research method was a Complete Randomized Block Design (CRBD) in factorial with 3 replications, consists of two factors : RPO and skim milk formulation (25:75), (50:50), (75:25), (100:0), and type of stabilizer (gelatin and CMC). The data was processed furtherly by orthogonal comparison. The research results showed that RPO and skim milk formulations affect the ice cream characteristics and carotenoid total significantly, while the type of stabilizer only affect the characteristics of the ice cream. Interactions between RPO and skim milk formulations compared to the type of stabilizer only affect the characteristics of ice cream but did not affect the carotenoid total. The best product is an ice cream with RPO and skim milk formulations 25:75 and CMC as stabilizer with a characteristic melting speed (11.28 minutes) , overrun (10.35 %) , total solids (22.96 %) , carotenoidâs total (13,405ppm) , yellowish white color (1.9) , normal taste (3.45) , normal aroma ( 3.68) , soft texture (2.97) , and the preferred overall acceptance (2,833) .